Urgency of the Right to Recognition for Identity’s Belief as A Part of Human Rights - Wijayanti, Winda (Hasanuddin University, 2018)
The right of recognition a belief is one of the basic human rights set forth in the Constitution. Population Administration Act as the executor of the constitutional mandate does not regulate of information column’s ”Belief” in an identity card (KTP-el) or a blank religion is a legal vacuum. Many debates occurred during the discussion and after the enactment of the Population Administration Act that only regulates the administration of population and issues between Religion and Belief as being very sensitive so that discussion of belief is considered not the domain of the Population Administration Act. Then, the absence of public participation in discussion of amendment Population Administration Act as a form of non-recognition of the existence of Believer in regulation. The problem is no rule for public participation in Population Administration Act. In fact, this paper used a normative juridical approach, with qualitative descriptive about debate of the Administration Population Act (DPR) to find out the urgency of the right to recognition for identity’s Belief through KTP-el. The result showed that inclusion of information column’s “Belief” is an entrance (gate) for the state's recognition of the people’s belief and their constitutional rights attached to it. Not only through words, but the recognition of the state through the State Administrators is manifested by legislation and communication (dialogue) between state and its citizens to remove all the existing attributes with equally, parallel, and continuously.